META-ANALYSIS REVIEW OF THE USE OF VIRTUAL REALITY IN SAFETY TRAINING - Ariyanto, Stefanus Timonora Wahyu; Noviah, Ema; Riyadi, Riyadi; Sarifah, Iva (IJBLE Scientific Publications Community Inc., 2023)
This study aims to review the use of virtual reality in safety training through a meta-analysis approach. The choice of topics in this study was motivated by the lack of studies related to correlations that discuss Virtual Reality